KAJIAN KEMAMPUAN GURU GEOGRAFI DALAM PENGELOLAAN KELAS DI SMA NEGERI 2 TONDANO - Keysia Mokodaser; Hermon Maurits Karwur; Xaverius Erick Lobja (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2021)
The research problem is to determine the ability of geography teachers in managing classes at SMA Negeri 2 Tondano. This study used qualitative research methods with the research informants is geography teachers, amounting to 3 teachers with data collection techniques through observation, interviews, and documentation. The results of this study indicate that 1) the skills to create a good learning atmosphere, the geography teacher of SMA Negeri 2 Tondano have provided instructions, given admonitions, gave verbal and visual attention and focused attention in learning, 2) the ability of class mastery in the learning process with steps the teacher does, namely creating good interactions, creating a good atmosphere, creating learning flexibility and instilling discipline, 3) the ability to manage the interaction of learning activities, the steps taken by the teacher, namely focusing attention in learning, providing clear instructions about learning, providing reinforcement, provide motivation, and give admonitions and organize the learning space, 4) classroom arrangement skills with the steps the teacher takes in relation to class arrangement skills in the form of arranging student seating positions and preparing students to receive lessons, arranging the location of facilities who are in the classroom and organize the study room.